Electrical machines : an objective and viva voce approach - Ankur Mathur (New Delhi CBS Publishers and Distributors Pvt Ltd, 2016)
This textbook will be of great help not only to the undergraduate and postgraduate students of pathology, but also of deep interest to the pathologists, hematologists and concerned clinicians. It will be a useful guide for day-to-day reporting in hematology and prove useful for the students appearing for the examinations.
Keywords: Direct Current Generator; Direct Current Motor; Single Phase Transformer; Three Phase Induction Motor